Effectiveness and mechanisms of mesenchymal stem cell therapy in preclinical animal models of hepatic fibrosis: a systematic review and meta-analysis - Wang, Xuesong; Wang, Yue; Lu, Wenming; Qu, Jiayang; Zhang, Yang; Ye, Junsong (Frontiers in Bioengineering and Biotechnology, 2024)
Liver damage due to long-term viral infection, alcohol consumption, autoimmune decline, and other factors could lead to the gradual development of liver fibrosis. Unfortunately, until now, there has been no effective treatment for liver fibrosis. Mesenchymal stem cells, as a promising new therapy for liver fibrosis, can slow the progression of fibrosis by migrating to the site of liver injury and by altering the microenvironment of the fibrotic area.By including all relevant studies to date to comprehensively assess the efficacy of mesenchymal stem cells for the treatment of hepatic fibrosis and to explore considerations for clinical translation and therapeutic mechanisms.Data sources included PubMed, Web of Science, Embase, and Cochrane Library, and were constructed until October 2023. Data for each study outcome indicator were extracted for comprehensive analysis.The overall meta-analysis showed that mesenchymal stem cells significantly improved liver function. Moreover, it inhibited the expression level of transforming growth factor-β (SMD=4.21, 95%CI [3.02,5.40]), which in turn silenced hepatic stellate cells and significantly reduced the area of liver fibrosis (SMD=3.61, 95% CI [1.41,5.81]).Several outcome indicators suggest that mesenchymal stem cells therapy is relatively reliable in the treatment of liver fibrosis. The therapeutic effect is cell dose-dependent over a range of doses, but not more effective at higher doses. Bone-marrow derived mesenchymal stem cells were more effective in treating liver fibrosis than mesenchymal stem cells from other sources.